Analysis of IP Valuation Product of LIPI IDP000040604 as Marketing Strategy for Promotion of Innovative and Inventive Activities - Nasution, Syukri Yusuf (School of Business and Management Institut Teknologi Bandung, 2017)
Abstract. IP Valuation means the process of how to compare object patented (protected) and its characteristics with the similar to gain a benefit. In this research, the product that value has been registered and certified for the patent in Indonesia with number IDP000040604. IP Valuation conducted to estimate the potential future economic benefit of this product. Qualitative and quantitative methods carry out to determine the value of IP. A qualitative method performed by in-depth analysis for Legal, Technology, Market and Finance indicators. A quantitative method conducted to determine the value of IP by using income approach with DCF method. From the qualitative analysis it shows that the product is in low risk and high opportunity quadrant, and from quantitative analysis, it shows that the NPV of the product is Rp.52.088.550,- with a royalty rate of 7% with estimated turnover about Rp.692.921.848,- for 10 years of useful economic life.Keywords: IP Valuation, future economic benefit, qualitative and quantitative methods, high opportunity, royalty rate